Events in social networks : a stochastic actor-oriented framework for dynamic event processes in social networks - Stadtfeld, Christoph (KIT Scientific Publishing, 2012)
Interactions between people are ubiquitous. When people make phone calls, transfer money, connect on social network sites, or visit each other, these actions can be collected as dyadic, directed, relational events. Each of those events can be understood as driven by multiple individual decisions that at least partially involve rational considerations. This book aims at developing models that allow to understand individual event decisions in the context of large social networks.